Rafał Łatka, Beata Mackiewicz, ks. Dominik Zamiatała, Prymas Stefan Wyszyński. Biografia - Lech Mażewski (Czasopismo Prawno-Historyczne)
Rafał Łatka, Beata Mackiewicz, ks. Dominik Zamiatała, Prymas Stefan Wyszyński. Biografia